Implementasi Penggunaan Turutan Sebagai Alternatif Belajar Membaca Al-Qur’an Bagi Pemula: (Studi Kasus di Madin Al-Farabi, Cabean Kota Salatiga) - Muhammad Fahri Abid (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses applying the Baghdadiyah method using the Turutan book as an alternative teaching approach for beginners learning to read the Qur'an at Madrasah Diniyah Al-Farabi, Cabean, Salatiga City. The Qur'an is a holy book, and one must understand and be well-versed in the correct tajweed rules. The Baghdadiyah method, also known as the sequence method, was chosen to improve students' reading skills. This study employed a qualitative field research approach to observe the teaching and learning environment at Madrasah Diniyah Al-Farabi. The research findings indicate that although many students find it challenging to learn the Qur'an, this method helps students comprehend hijaiyah letters and tajweed. The advantages of this method include its clear structure and ease of use, though it does have some drawbacks, such as requiring intense focus and pressure for memorization. Nonetheless, the method is considered effective for beginners in learning the Qur'an.